pH- and time-resolved in situ SAXS study of self-assembled twisted ribbons formed by elaidic acid sophorolipids - Dhasaiyan, Prabhu; Prevost, Sylvain; Baccile, Niki; Prasad, Bhagavatula L. V. (Langmuir, 2018)
Conditions that favor the helical structure formation in structurally similar sophorolipids (SLs), that is, elaidic acid SLs (having a trans double bond between the C9 and C10 positions of the alkyl chain) and stearic acid SLs (no double bond), are presented here. The helical self-assembled structures formed by elaidic acid SLs were independent of pH and also were mediated by a micellar intermediate. On the other hand, the stearic acid SLs formed helical structures under low pH condition only. Astonishingly, the formation routes were found to be different, albeit the molecular geometry of both SLs is similar. Even if a conclusive mechanistic understanding must await further work, our studies strongly point out that the noncovalent weak interactions in elaidic acid SLs are able to overcome the electrostatic repulsions of the sophorolipid carboxylate groups at basic pH and facilitating the formation of helical structures. On the other hand, the hydrophobic interactions in stearic acid SLs endow the helical structures with extra stability, making them less vulnerable to dissolution upon heating.